Pacifist Empowerment of the Current Peace Process in Colombia: 2012-2015 - Esperanza Hernández Delgado (Revista de Paz y Conflictos, 2015)
Colombia has been an internal armed conflict that has over half a century and is identified within the oldest. This country is also evidence, an important cumulative learning in peace processes; and the search for a negotiated end of the conflict, by governments and insurgent movements in the past thirty- three years. However, so far it not achieved the desired final peace agreement with all insurgent movements, leaving the country in a permanent limbo: neither peace nor total war; nor peace negotiations with the expected scope, or defeat the enemy. It is in this context that this paper feed, product of a research exercise for peace, conducted with the Institute of Political Studies at the Autonomous University of Bucaramanga -UNAB- , is located and focused on the peace process, since October 2012, a head President Juan Manuel Santos and the rebel movement Farc Ep. The object of the research was to characterize this peace process in order to produce academic knowledge around itself, and learning from it since the peacebuilding perspective. It was made from the historical - sociological analysis methodological model. Researchers consulted relevant primary and secondary sources. The first sources, represented in 35 semi –structured interviews with academic experts, peace negotiators, not academic experts and builders of peace. Considering that peace negotiations are still ongoing, this article presents partial findings, represented in one of its essential characteristics: build an experience of «pacifist empowerment».